PENDIDIKAN KARAKTER DISIPLIN SISWA DI ERA MODERN SINERGI ORANG TUA DAN GURU DI MTs NEGERI KABUPATEN KLATEN - Sri Hartini (AL-ASASIYYA: Journal Of Basic Education, 2017)
There is a relation that can not be ignored between the synergy of parents and teachers in character education discipline students. Relationships both occur in two directions, on the one hand, synergy parents and teachers play a role in shaping the behaviour of student discipline character. On the other hand, the view of certain disciplinary characters also becomes the catalyst for the emergence of other distinctive characters of discipline. In the context of character education of discipline students in the modern era, synergy of parents and teachers at Madrasah Tsanawiyah Negeri in Klaten District found an extension of synergy between parents and teachers with the phenomenon of disciplinary character education students who worry. While the factors causing the destruction of the character of students in MTN Negeri Klaten district is influenced by teachers and parents, and the education system imposed in the madrasah.